2022
DOI: 10.3390/jcm11237078
|View full text |Cite
|
Sign up to set email alerts
|

Combined Airway and Bariatric Surgery (CABS) for Obstructive Sleep Apnea Patients with Morbid Obesity: A Comprehensive Alternative Preliminary Study

Abstract: Although continuous positive airway pressure is the gold standard for obstructive sleep apnea (OSA), it does not improve obesity. By contrast, bariatric surgery significantly improves obesity but with sustained OSA in the majority of patients. This study proposes a comprehensive technique—combined airway and bariatric surgery (CABS)—to improve both obesity and OSA. The aims of the study are to evaluate the feasibility, safety and efficacy of CABS in morbidly obese OSA patients. The retrospective study enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Patients with morbid obesity have different degrees of abnormal fat distribution and accumulation in tissues throughout the body, which results in a large amount of soft-tissue hyperplasia in the oropharynx, muscle relaxation, sagging, and hyperplasia of the tongue, leading to a relative reduction in the volume of the oropharyngeal cavity and a relative reduction in the upper part of the tongue, leading to a decrease in the volume of the oropharyngeal cavity and a narrower upper airway. As a result, patients with morbid obesity tend to have comorbid obstructive sleep apnea syndrome and a high risk of difficult airway ( 4 ). Excessive thoracic and abdominal fat leads to thoracic and lumbar lordosis, limiting intercostal muscle movement and thoracic expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with morbid obesity have different degrees of abnormal fat distribution and accumulation in tissues throughout the body, which results in a large amount of soft-tissue hyperplasia in the oropharynx, muscle relaxation, sagging, and hyperplasia of the tongue, leading to a relative reduction in the volume of the oropharyngeal cavity and a relative reduction in the upper part of the tongue, leading to a decrease in the volume of the oropharyngeal cavity and a narrower upper airway. As a result, patients with morbid obesity tend to have comorbid obstructive sleep apnea syndrome and a high risk of difficult airway ( 4 ). Excessive thoracic and abdominal fat leads to thoracic and lumbar lordosis, limiting intercostal muscle movement and thoracic expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anatomic obstruction‐oriented upper airway surgery should also be considered in OSA patients with obesity 32 . Lin et al revealed that combined airway surgery and bariatric surgery achieve 90% success rate 33 . Therefore, we can use these DISE modification findings to adjust our future surgery and treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
“…32 Lin et al revealed that combined airway surgery and bariatric surgery achieve 90% success rate. 33 Therefore, we can use these DISE modification findings to adjust our future surgery and treatment protocol. That is, the integration of various conservative treatments, such as OA, positional therapy, intermittent negative airway pressure, weight control, and several kinds of surgical treatments, may effectively treat OSA, especially CCC.…”
Section: Discussionmentioning
confidence: 99%